2014
DOI: 10.1002/jbm.a.35226
|View full text |Cite
|
Sign up to set email alerts
|

Biological protein‐resistance layer construction of recombinant hirudin on polymethyl methacrylate IOL surface

Abstract: In this article, the surface of intraocular len material PMMA was first aminated for activation on which some polar groups generated such as C-N, COO(-), -OH, NH3(+), etc. Then the anticoagulant drugs recombinant hirudin (rH) was grafted with amido bonds to look forward to resist the adsorption of nonspecific protein or cells in tear, even the cataract. The detailed analysis and discussion about the grafting quantity, molography, wettability, electric charges, chemical structure, and the dynamic adsorption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…3d). BSA adsorption on IOL was 130.8 ± 9.9 ng/cm 2 , which was similar to that on other hydrophobic IOL surfaces we previously reported36. Compared to IOL , BSA adsorption on IOL-Plasma decreased to 43.1 ± 8.2 ng/cm 2 , and BSA adsorption on IOL-P ( MPC-MAA ) further decreased to 14.5 ± 3.1 ng/cm 2 .…”
Section: Resultssupporting
confidence: 86%
“…3d). BSA adsorption on IOL was 130.8 ± 9.9 ng/cm 2 , which was similar to that on other hydrophobic IOL surfaces we previously reported36. Compared to IOL , BSA adsorption on IOL-Plasma decreased to 43.1 ± 8.2 ng/cm 2 , and BSA adsorption on IOL-P ( MPC-MAA ) further decreased to 14.5 ± 3.1 ng/cm 2 .…”
Section: Resultssupporting
confidence: 86%
“…Combined with previous research results, it is found that ammonia plasma has the ability to improve the hydrophilicity of acrylic esters and PMMA. It not only introduces some polar groups containing elemental N onto the material surface (NH 2 or CON), but also gives the surface a certain positive charge, such as in the case of the amine cation  NH3+/N + (CH 3 ) 3 , without changing the material mechanical properties.…”
Section: Discussionsupporting
confidence: 72%
“…A functional construction model of biomedical polymer surfaces is shown in Figure , which illustrates the progress in achieving resistance to nonspecific adsorption. Previous studies have shown that some functional modifications can resist the nonspecific adsorption of proteins, such as amphipathic 2‐methacryloyloxyethyl phosphorylcholine (MPC) applied onto the surface of Polyethylene terephthalate (PET) cardiovascular materials or anticoagulant hirudin applied onto PMMA intraocular lens (IOL) surfaces . In this article, the biological behavior at the functional surfaces was evaluated by measuring cytotoxicity, cell proliferation, and with animal tests, using hydrophobic acrylic ester and polymethyl methacrylate (PMMA) in the research.…”
Section: Introductionmentioning
confidence: 99%
“…After the eye lens is removed by PHACO, implantation of an artificial intraocular lens (IOL) is performed. With respect to the materials of artificial eye lenses, lenses made from polymethyl methacrylate and silicon were mainly used, but hydrophobic acrylic lenses have been increasingly used in recent years (Zheng et al, 2015). Artificial eye lenses were generally spherical in shape, but aspherical lenses have been recently developed.…”
mentioning
confidence: 99%